THE EFFECT OF COLLABORATIVE PROBLEM SOLVING LEARNING MODELS ON MATHEMATICAL LEARNING RESULTS REVIEWED FROM THE ABILITY OF PROBLEM-SOLVING OF CLASS VII - Sekarwuni yhudanti; Nur Arina Hidayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2020)
This research is motivated because, in learning mathematics, students' problem -solving abilities are still low. Students have not been able to understand the problem given. This is Indicated by many students who cannot determine what is known and what is asked in the problem. This study aims to determine the Collaborative Problem Solving Learning Model (CPS) effect on Mathematics Learning Outcomes in Students' Mathematical Problem Solving Ability. This research is an experimental study with a research design using a 2-2 factorial design. The population of the study was all VII grade students of Junior High School (SMP) Muhammadiyah 3 Depok in the even Semester of the 2019/2020 school year. The sample used in this study was to take two classes. Randomly, namely, class VII A as a control class and VII D as an experimental class. Data collection Two techniques using the test. The data analysis technique used two-way Anava with prerequisite test analysis of normality test and homogeneity test and continued with LSD test. The results of this study can be concluded: (i) Fobs(A) > F0,05;1;66, there is an influence of learning model factors on mathematics learning outcomes, (ii) Fobs(A) < F0,05;1;66, there is no influence of students mathematical problem-solving ability factors on results students mathematics learning, (iii) Fobs(A) < F0,05;1;66, there is no interaction between the factors of the learning model and students mathematical problem-solving abilities towards student mathematics learning outcomes.